Surface with Reversible Green-Light-Switched Wettability by Donor-Acceptor Stenhouse Adducts - Zhao, Haiquan (Langmuir : the ACS journal of surfaces and colloids, 2018)
In this report, we designed surfaces with reversible green-light-switched wettability via donor-acceptor Stenhouse adducts (DASAs). Photoresponsive micro/nanoparticles were prepared by coating the surfaces of silica micro/nanoparticles with polydopamine and then postmodifying with DASA molecules. Then, the particles were immobilized on a glass substrate surfaces either with double-sided adhesive tape or cross-linking poly(dimethylsiloxane). Silica micro/nanoparticles with various diameters (0.2, 2.5, and 85 μm) were used to fabricate the photoresponsive surface. Green light irradiation switches the hydrophobic linear DASA to a hydrophilic cyclic isomer, which further increases the wettability and contact angle hysteresis on the surface. On the other hand, heating (100 °C) induces the cyclic-to-linear isomerization of DASA molecules and switches the surface back to hydrophobic. The wettability of the DASA-modified surface is reversible under alternate green light irradiation and heating